Relationship between Knowledge, Attitude and Behavior of Postnatal Woman Toward Participation in Permanent Contraception - Jhon Heriansyah; Azhari Azhari; Firmansyah Basir; Theodorus Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To investigate the association between knowledge,attitude, and behavior towards participation in permanentcontraception and describe factors that could affectparticipation of permanent contraception in women inRSMH Palembang.Methods: This case control study was conducted at the Departmentof Obstetrics and Gynecology, Dr. Mohammad Hoesin Hospital/Faculty of Medicine, Universitas Sriwijaya, Palembang, during theperiod of June 2016 to December 2016. Sample of the cases groupwas woman who agreed to use permanent contraception whilecontrol sample was women who refuse to use permanent contraception.Data were collected using a questionnaire. Statisticalanalysis was performed using SPSS.Results: There was a significant association between attitude,behavior, husband support, and disease complications withparticipation of permanent contraception. Factors that influencedparticipation of permanent contraception in woman in RSMHPalembang include husband support and behavior.Conclusion: Factors that influence the participation of women inRSMH safe contraception Palembang include support for herhusband and behavior.[Indones J Obstet Gynecol 2018; 6-1: 39-44]Keywords: family planning, participation, permanent contraception